2020
DOI: 10.2490/prm.20200007
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative Rehabilitation of Atypical Femoral Fracture in a Single Center

Abstract: Increasing numbers of reports have described atypical femoral fracture (AFF) in patients being treated with oral bone resorption inhibitors, such as bisphosphonates. Most AFF patients undergo surgical treatment. However, there is little information about post-operative rehabilitation and patient activity levels after surgery for such fractures. Here we report the outcome of surgical treatment and postoperative rehabilitation for AFF at a single center in Japan. Methods: We retrospectively reviewed 13 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…1 ). Among 29 studies, 11 cohort articles included both sites of AFF (subtrochanteric and midshaft), 7 13 16 17 18 19 20 21 22 23 24) 9 cohort studies reported outcomes after surgery of subtrochanteric AFFs, 6 9 10 11 14 25 26 27 28) and 9 single cohort studies reported midshaft AFF. 8 12 15 29 30 31 32 33) The overall incidence of nonunion was 10.3% (77 / 742) in total, 17.5% (52 / 297) in the subtrochanteric AFFs group, and 5.6% (25 / 445) in the midshaft AFFs group ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…1 ). Among 29 studies, 11 cohort articles included both sites of AFF (subtrochanteric and midshaft), 7 13 16 17 18 19 20 21 22 23 24) 9 cohort studies reported outcomes after surgery of subtrochanteric AFFs, 6 9 10 11 14 25 26 27 28) and 9 single cohort studies reported midshaft AFF. 8 12 15 29 30 31 32 33) The overall incidence of nonunion was 10.3% (77 / 742) in total, 17.5% (52 / 297) in the subtrochanteric AFFs group, and 5.6% (25 / 445) in the midshaft AFFs group ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%